“Who run the world?” Gender and the social network of R&B/hip hop collaboration from 2012 to 2020 - Cassie McMillan (Applied Network Science, 2022)
Abstract Part of the reason women are disadvantaged in the labor market is because gender inequalities define social networks of the workplace. In the current project, I consider how gender shapes professional networks by focusing on the R&B/hip hop industry as an empirical case study. By conceptualizing the collaboration patterns between performers of popular R&B/hip hop songs from 2012 to 2020 as a network, I apply exponential random graph models (ERGMs) and find that women tend to occupy marginalized positions when compared to their male peers. Then, I adopt a social exchange framework to argue that critical acclaim is a resource that is associated with higher odds of collaborating for all artists, though gender differences define this process. For instance, the largest gender gaps in collaboration are present among artists who have either won Grammy awards or never received nominations for such honors. These findings suggest that female artists with lower status are often excluded from collaboration opportunities. Once women acquire enough prestige to “make up” for their gender, they may avoid collaborations because gender stereotypes challenge their decision-making power within these interactions.